2008
DOI: 10.1007/s11661-008-9500-y
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Processing of ZrB2-ZrC Composites by Reactive Hot Pressing

Abstract: LINGAPPA RANGARAJ, SIRIYARA J. SURESHA, CANCHI DIVAKAR, and VIKRAM JAYARAM Dense ZrB 2 -ZrC and ZrB 2 -ZrC x~0.67 composites have been produced by reactive hot pressing (RHP) of stoichiometric and nonstoichiometric mixtures of Zr and B 4 C powders at 40 MPa and temperatures up to 1600°C for 30 minutes. The role of Ni addition on reaction kinetics and densification of the composites has been studied. Composites of~97 pct relative density (RD) have been produced with the stoichiometric mixture at 1600°C, while t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 35 publications
4
55
1
3
Order By: Relevance
“…To account for that we have modified the model of Helle et al [25][26][27] Constitutive equations are shown in Eq. (2)(3)(4)(5).…”
Section: (4) Densification Mechanism In Rhp Of Zrc Xmentioning
confidence: 99%
See 2 more Smart Citations
“…To account for that we have modified the model of Helle et al [25][26][27] Constitutive equations are shown in Eq. (2)(3)(4)(5).…”
Section: (4) Densification Mechanism In Rhp Of Zrc Xmentioning
confidence: 99%
“…4 Reactive hot pressing (RHP), on the other hand, showed more promise and recent work on RHP of zirconium (Zr) -boron carbide (B 4 C) and Zr: carbon (C) powder mixture yielded full density at much lower temperatures. [5][6][7] Stoichiometric 3Zr:B 4 C composition required 1600°C and 40 MPa to achieve 96% relative density (RD), whereas nonstoichiometric 3.5Zr:B 4 C composition yielded 98% RD at a significantly lower temperature of 1200°C. 5 The study on RHP has been extended to different molar ratios of Zr:C and it was observed that the nonstoichiometric composition always displayed a better densification than the stoichiometric composition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3. The calculated values of increments of the fracture toughness KIC for the composite materials ZrB 2 -SiC, ZrB 2 -ZrC, ZrB 2 -TiB 2 when the volume concentration of inclusions are of 10 -20 % [1,4,13,19,20].…”
Section: Resultsmentioning
confidence: 99%
“…The material sintered at 1873 K (1600°C) displayed mechanical properties comparable to those previously reported for materials that had experienced higher sintering temperatures. Rangaraj et al [75,76] found that nonstoichiometric ZrC x played a crucial role in RHP of Zr-B 4 C powder mixtures at 1473 K (1200°C) and in ZrB 2 -SiC composites produced at 1873 K (1600°C).…”
Section: Reactive Hot Pressingmentioning
confidence: 99%